2023
DOI: 10.1039/d3tb00478c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-based hydrogels for drug delivery

Abstract: This article presents a comprehensive review of the preparation methods, carrier forms, and key parameters of nanocellulose-based hydrogels as drug delivery systems. And it proposes potential research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 180 publications
(230 reference statements)
0
3
0
Order By: Relevance
“…Hydrogels represent a class of polymeric biomaterials that have garnered considerable attention in the field of drug delivery and biomedical applications due to their unique characteristics. These three-dimensional networks consist of hydrophilic polymer chains, which imbue them with a high water content, typically ranging from 90 % to 99 % [ 32 ]. This remarkable feature renders hydrogels highly biocompatible and well-tolerated by living tissues, making them particularly suitable for a wide array of medical applications.…”
Section: Different Types Of Polymeric Ddsmentioning
confidence: 99%
“…Hydrogels represent a class of polymeric biomaterials that have garnered considerable attention in the field of drug delivery and biomedical applications due to their unique characteristics. These three-dimensional networks consist of hydrophilic polymer chains, which imbue them with a high water content, typically ranging from 90 % to 99 % [ 32 ]. This remarkable feature renders hydrogels highly biocompatible and well-tolerated by living tissues, making them particularly suitable for a wide array of medical applications.…”
Section: Different Types Of Polymeric Ddsmentioning
confidence: 99%
“…The drug delivery capacity of implantable materials is an important factor in improving their performance. For effective drug delivery, the introduction of mediators such as drug carriers and hydrogels or physical methods such as creating micropores on a material surface have been investigated [5][6][7][8]. In particular, to store and deliver drugs, it has been reported that micropores can be formed on the material surface using laser-based physical surface modification methods such as ion beam and femtosecond laser irradiation or chemical surface modification methods such as anodic oxidation and polishing [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…have been reported, which is expected to heighten the efficacy and safety of DOX. Despite significant advancements, simple delivery systems could be prone to causing premature drug leakage, failing to achieve an effective drug therapeutic concentration at the focal site. Besides, these delivery systems often require complicated synthetic materials, which may bring about a tedious preparation process and increase the cost. Therefore, there remains a surging anticipation for developing a novel simple and effective delivery strategy for HCC therapy.…”
Section: Introductionmentioning
confidence: 99%